αvβ3-specific gold nanoparticles for fluorescence imaging of tumor angiogenesis - Pretze, Marc; Kiedrowski, Valeska von; Runge, Roswitha; Freudenberg, Robert; Hübner, René; Davarci, Güllü; Schirrmacher, Ralf; Wängler, Carmen; Wängler, Björn (Nanomaterials, 2021)
This paper reports on the development of tumor-specific gold nanoparticles (AuNPs) as theranostic tools intended for target accumulation and the detection of tumor angiogenesis via optical imaging (OI) before therapy is performed, being initiated via an external X-ray irradiation source. The AuNPs were decorated with a near-infrared dye, and RGD peptides as the tumor targeting vector for αvβ3-integrin, which is overexpressed in tissue with high tumor angiogenesis. The AuNPs were evaluated in an optical imaging setting in vitro and in vivo exhibiting favorable diagnostic properties with regards to tumor cell accumulation, biodistribution, and clearance. Furthermore, the therapeutic properties of the AuNPs were evaluated in vitro on pUC19 DNA and on A431 cells concerning acute and long-term toxicity, indicating that these AuNPs could be useful as radiosensitizers in therapeutic concepts in the future.
Gesehen am 04.05.2021